Pengembangan Instrumen Tes Tingkat Literasi Statistik Mahasiswa - noviantari, ika; Mansur, Musyafira (Program Studi Pendidikan matematika STKIP PGRI Pacitan STKIP PGRI Pacitan, 2023)
This study has the objective of developing a student statistical literacy test. It is hoped that the test instrument can measure students' statistical literacy skills with instruments that are valid in terms of content and constructs. In this study the instrument was developed in three stages, namely introduction, planning and development. For content validity, it was carried out by 5 experts. As for the construct validity using confirmatory analysis, Goodness of Fit and model reliability. The validity results show that each item is measured by 5 aspects of statistical literacy indicators. The RMSEA value is 0.062 which is between 0.05 and 0.08, CFI and GFI is 1.00 which means the statistical literacy model is in the good fit category. Statistical literacy values ​​were obtained from trials on 50 students in the city of Tarakan, North Kalimantan with good construct reliability test results where the construct reliability (CR) value of each latent variable was 0.73 ≥ 0.70 with a Variance extracted (VE) value of 0.58 ≥ 0.5. The conclusion is that the developed statistical literacy instrument meets valid and reliable constructs to measure students' statistical literacy levels.